KOMPARASI RANGKAIAN SENSOR GARIS DENGAN LM 741 DAN TLC 274 PADA ROBOT MOBIL PENGIKUT GARIS (LINE FOLLOWER) DENGAN MENGGUNAKAN MIKROKONTROLER ATMega 8535 - Djulil Amri (Jurnal Rekayasa Sriwijaya, 2010)
Line Follower Robot is one of autonomous mobile robot form that has mission following autonomously the guided line. In its design and implementation, many problems that should be solved. The problemsÂ  that should be solved are system of robot vision, architecture of hardware including electronics and mecanics, and organizations of software for knowledge base and real time control. The purpose of this final assignment is to find out the combination of an accurate censor in order to the automobile line follower robot be able easily to differentiate and detect the white path with the red, green and blue as background. The replacement of some IC as signal processing and also the use of some LED colors as transmitter on line censor give influence to the reading and work of censor. The result of the test, the average velocity of line censor by using LM 741 is 1 minute 34 second, while the average velocity of line censor by using TLC 274 is. The transmitter by using super bright white LED is the most accurate transmitter to automobile line follower robot.